Человек - субъект капитала, как проблема - Кухар, В.В. (Культура народов Причерноморья, 2013)
Обоснование понятия человека как субъекта капитала сегодня в научных исследованиях
отсутствует. Человек тоже не может быть капиталом, что превращает его в средство - винтик
государства. В предлагаемой статье автор пытается разрешить возникшую проблему. Он исследует
тенденцию движения капитала от частного состояния к особенному - человеку-капиталу и от него к
обществу-капиталу. Идея субъекта человека-капитала выдвинута автором в диссертации, став
предметом его научных изысканий, представляя собой инновационное и актуальное содержание. По
исследуемой проблеме автором опубликован цикл статей, она присутствует в его учебно-методических
пособиях и материалах последнего времени, а также в одной из монографий. Обґрунтування поняття людини як суб'єкта капіталу сьогодні в наукових дослідженнях
відсутня. Людина теж не може бути капіталом, що перетворює його на засіб - гвинтик держави. У
запропонованій статті автор намагається вирішити виниклу проблему. Він досліджує тенденцію руху
капіталу від приватного стану до особливого - людині-капіталу і від нього до капіталу суспільства-
капіталу. Ідея суб'єкта людини-капіталу висунута автором у дисертації, ставши предметом його
наукових вишукувань, представляючи собою інноваційний та актуальний зміст. З досліджуваної
проблеми автором опубліковано цикл статей, вона присутня в його навчально-методичних посібниках і
матеріалах останнього часу, а також в одній з монографій. Justification concept of human capital as a subject in research today is missing. A person also can
not be capital, which turns it into a tool - a cog of the state. In this article, the author attempts to resolve the
problem. He explores the trend of capital flows from the private to the particular condition - a human capital
and from there to the public - capital. The original link traffic - human-capital. In such a complex
transformation connects two complementary ways. First, the person must be the capital, and second, then all
surrounding things and objects in need of recreation, it is necessary to turn to the capital. The method is based
on the transformation of the human ability to make much more money than individual consumption. Society has
progressed through the process of production, exchange and consumption, in which the people, improving the
tools, increases the productivity of the work force and their intelligence, but he is not able to become the capital.
Therefore, it must be in it capital: the main value, creative self-sufficient entity, able to transform society, nature,
adapting itself to them.
The idea of the subject of human capital in the thesis put forward by the author, becoming the subject of his
scientific research, introducing an innovative and relevant content. On the problem at the author published a
series of articles, it is present in his teaching aids and materials of recent times, as well as one of the
monographs.